Perceptions of the Teaching Profession and Its Professionalisation in Spain - Monarca, Héctor; Rappoport, Soledad; Pericacho, Javier; Mottareale, Daria; Gratacós, Gloria; Azorín, Cecilia; Ruiloba, Juana; Messina, Claudia (European Journal of Education, 2024)
The article is based on a novel theoretical framework for studying the teaching profession and its professionalisation from a broadview of Education as a common field in which many different actors take part. The way the field of Education is (re)produced israrely researched. Rather, its current order is assumed as valid, ignoring the infighting between different actors to control andlegitimise particular areas of knowledge, know-how and practices that comprise it as a field. The article presents a survey-basedstudy with the following objectives: (1) identify how the teaching faculty perceive the structural and structuring aspects of theteaching profession in the field of education and (2) analyse how those aspects affect the development of a horizontally, democrat-ically and collaboratively articulated profession and its professionalisation with all the other fields in education. The survey wastaken by 7145 preschool, primary and secondary teachers at schools in Spain. The results show the structural and structuringfeatures of a field of education, in tatters, differentiated and hierarchical, characterised by an uneven distribution of opportuni-ties for its actors to ‘say’, ‘do’ and ‘decide’. At the same time, the results offer a chance to explore a more horizontal articulation ofthe teaching profession and its professionalisation within the field of education.
Keywords: field of education; professionalisation; Spain; survey study; teaching profession